A Performance Comparison Of C# 2013, Delphi Xe6, And Python 3.4 Languages - KARACI, Abdulkadir (Zenodo, 2015)
C# 2013, Delphi XE6, and Python 3.4 are the newest and most popular programming languages. These programming languages become more popular every passing day. In this study, the response times, memory usages, and code lengths of these languages were tested in various workloads. Whether or not there was any significant difference between the data obtained from workloads was tested via the Friedman test. The test indicated a significant difference. In addition, the Wilcoxon signed rank test was used for determining the effect size. This test showed that the level of the significant difference found in the Friedman test was high
Keywords: C#, Delphi XE6, Performance Test, Python, Programming Language; Delphi XE6; Performance Test